Quasi-Square sinusoidal pulse width modulated grid-tie inverter - Torres, Jan Vincent T. (2009.)
A way to constantly extract the maximum power from renewable energy sources is to feed the extracted power to the utility grid when the local energy storage is full. This line-feeding circuit is called a grid-tie inverter (GTI). GTIs inject in-phase AC current to the grid from a DC source while the grid is in operation. This way, renewable energy may be extracted regardless of battery charge status. Furthermore, cost of grid power transmission and generation from lumped generation may be lessened by wide implementation by this scheme. Effectiveness of a GTI may be assessed with the quality of the current it delivers. Proper AC current synchronization allows the maximum power factor and minimal reactive power consumption of the inverter. The project deals with the design and the construction of a single-phased non-isolated GTI from a high voltage Dc (HVDC) source. The full bridge topology was adopted due to its high power capacity and low cost. Switches were controlled using high frequency unipolar sinusoidal pulse width modulation (SPWM) switching to maximize reduction of size and cost of the GTI-to-grid filter link. Benefits of unipolar SPWM switching were further improved by power-frequency quasi-square switching of low-side switches and decreased the possibility of cross conductance. A second order low-pass LCL T-network filter was devised to reduce the high frequency components of the output current using a small filter link. GTI output current synchronization was achieved by using a constant phase advanced sinusoid reference for the SPWM. The amount of this phase advance may be directly computed from the power frequency equivalent circuit of the GTI. Disturbances which account for variations in amplitude of the grid voltage and the HVDC ripple were limited by feeding-forward the respective sources. A sinusoidal reference current limiter restricts the output current from reaching excessive values.
Thesis (B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman.
Keywords: Electric inverters; Electric current converters; Photovoltaic power systems; Grid-tie inverter; Sinusoidal pulse